Implementing Inclusive Education in Resource-Constrained Primary Schools: A Comparative Case Study of Management Strategies in West Java, Indonesia - Silviani, Alien; Mulyanto, Agus (Papanda Publisher, 2025)
Inclusive education implementation faces significant challenges in Indonesian primary schools despite government regulations mandating equal educational access for children with special needs. This study examines inclusive education implementation through systematic management analysis in two primary schools with contrasting implementation contexts and timelines. A qualitative case study approach was employed using W. Edwards Deming's Plan-Do-Check-Act (PDCA) management framework to analyze inclusive education implementation at SDN Sukasari Indah (Bandung Regency) and SDN 201 Sukaluyu (Bandung City). Data collection utilized in-depth interviews with educators, parents, and students, direct classroom observations, and document analysis. Systematic analysis examined planning processes, implementation strategies, evaluation mechanisms, and follow-up actions across both schools. Both schools successfully implemented inclusive education despite resource constraints through strategic planning, collaborative learning approaches, and comprehensive evaluation systems. SDN Sukasari Indah leveraged fifteen years of experience to develop community partnerships and learning communities, while SDN 201 Sukaluyu established inclusion teams and professional consultation arrangements. Primary challenges included absence of specialized assistant teachers, limited systemic support, and inadequate teacher training. Both schools demonstrated innovative solutions including peer support systems, parent collaboration, and external partnerships with specialized organizations. Findings reveal that systematic management approaches enable effective inclusive education delivery despite systemic limitations. The research contributes to understanding locally-developed strategies that address resource constraints while maintaining commitment to inclusive principles, demonstrating institutional resilience and adaptability in delivering equitable education for all children including those with special needs.